Penerapan Metode Bermain Peran (Role Playing) dalam Pembelajaran Berbicara Bahasa Makassar Siswa Kelas V UPT SDN 167 Inpres Malewang Kabupaten Takalar (Journal of Applied Linguistics and Literature, 2024)
The purpose of this research is to describe the results of the speaking skills of fifth-grade students at UPT SDN 167 Inpres Malewang, Takalar District, through the application of the role-playing method. This research is of a quantitative nature. Data collection in this research was carried out through testing techniques on the research sample. The overall data obtained were analyzed through several stages: 1) creating a raw score list, 2) creating a frequency distribution and raw score, 3) calculating the scores obtained by students, and 4) classifying students' skills based on the specified criteria. The research results indicate that students who scored 75-100 were 15 individuals (75%) out of 20 samples and have achieved the established criteria, which is 75% of the samples scoring 75-100. It is evident from the scores and percentages of fifth-grade students at UPT SDN 167 Inpres Malewang, Takalar District, in learning to speak the Makassar language through the application of the role-playing method that they are categorized as skilled.